In Vitro Antibacterial and Antioxidant Activities and Molecular Docking Analysis of Phytochemicals from Cadia purpurea Roots - Tsegu Kiros; Rajalakshmanan Eswaramoorthy; Yadessa Melaku; Aman Dekebo (Journal of Tropical Medicine)
Phytochemicals and antibacterial and antioxidant activities of Cadia purpurea roots were investigated herein for the first time. The phytochemical study led to the isolation of two compounds, di-(2-methylheptyl) phthalate (1) and 13-O-pyrrolecarboxyl lupanine (2), from methanol roots extract of C. purpurea. The antibacterial activity results revealed that the n-hexane extract presented a better inhibitory value (13.8 ± 0.0 mm) followed by chloroform (11.1 ± 0.4 mm) and chloroform : methanol (1 : 1) (10.7 ± 0.1 mm) extracts against E. coli at the maximum dose of 100 mg/mL. While, methanolic and ethanolic extracts displayed a mild activity against same bacterium at same dose. The methicillin resistant S. aureus was found with almost total resistance to all extracts up to the 100 mg/mL. The chloroform : methanol (1 : 1), chloroform, and n-hexane extracts recorded inhibition zone values (8.0 ± 0.0–10.0 ± 0.1 mm, 7.7 ± 0.0–9.8 ± 0.1 mm, and 7.3 ± 0.2–8.9 ± 0.2 mm, respectively) better than chloramphenicol (7.2 ± 0.6 mm at 30 μg dose) against P. aeruginosa. The alcoholic extracts also exhibited an activity better than chloramphenicol up to 25 mg/mL against same bacterium. Compound 2 produced a comparable inhibition value (9.6 ± 0.0 mm to 18.5 ± 0.0 mm) to that of chloramphenicol (21.5 ± 0.3 mm) against E. coli at doses up to 1.0 mg/mL; whereas, compound 1 showed a slight activity (7.1 ± 0.1 mm–10.3 ± 0.0 mm). Both compounds were found generally inactive against S. aureus, while they provided an activity better than chloramphenicol (7.2 ± 0.6 mm) against P. aeruginosa with inhibition zones ranging from 7.1 ± 0.0 mm to 9.0 ± 0.1 mm for compound 1 and 7.2 ± 0.0 mm to 10.6 ± 0.0 mm for compound 2. Ethanolic and methanolic extracts exhibited a better DPPH radical scavenging activity (IC50 values of 12.9 and 16.03 μg/mL, respectively) and strong ferric ion reducing power (with absorbance of 0.788 ± 0.000 and 0.810 ± 0.001, respectively) at a concentration of 500 μg/mL compared to the other extracts. Compound 1 also possessed a better anti-DPPH trapping activity (IC50, 7.99 μg/mL) than compound 2 (IC50, 58.34 μg/mL). The compounds, however, indicated a weak ferric ion reduction power even at higher amount. In general, the observed antibacterial and antioxidant activities of isolated compounds and extracts were found to be dose-dependent. Conducting further biochemical investigations on all parts of this plant could provide opportunities of finding extra alkaloidal compounds and other phthalate derivatives with better biological activity.